Is profitability driven by working capital management? Evidence for high-growth firms from emerging Europe - Boțoc, Claudiu; Anton, Sorin Gabriel (Journal of Business Economics and Management, 2017)
Despite the importance of high-growth firms (HGFs) for job creation, innovation, and economic development in transition economies, current knowledge on the role of financial decisions in explaining their profitability is limited. The aim of this paper is to examine the relationship between working capital management and firm profitability. Using a panel data set on HGFs from Central, Eastern, and South-Eastern Europe during the time span 2006–2015, we found an inverted U-shape relationship between working capital level and firm profitability. Our findings indicate that HGFs should find and maintain the optimal working capital level that maximizes their profitability. Our results proved to be robust when we employ different methodology (quantile regression), different sub-samples as well as alternative measures of profitability and working capital management. The study highlights the importance of short-term financial decisions in enhancing HGFs’ profitability, with significant implications for academics and practitioners. We contribute to the extant literature by providing empirical evidence on the existence a concave relationship between working capital level and firm profitability for a cross-country sample of firms.